2011
DOI: 10.1111/j.1365-2893.2010.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Very early prediction of response to HCV treatment with PEG‐IFN‐alfa‐2a and ribavirin in HIV/HCV‐coinfected patients

Abstract: The objective of the present study was to find very early viral kinetic markers to predict nonresponse to HCV therapy in a group of HIV/HCV-coinfected patients. Twenty-six patients (15 HCV genotype-1 and 11 genotype-3) were treated with a 48-week regimen of peginterferon-alfa-2a (PEG-IFN) (180 μg/week) and weight based ribavirin (11mg/kg/day). Samples were collected at baseline; 4, 8, 12, 18, 24, 30, 36 and 42 hours; days 2, 3, 4, 7, 8, 15, 22, 29, 43 and 57 then weekly and monthly. Five patients discontinued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…In contrast, we did not identify a significant (p=0.5) difference in IL28B genotype frequencies between African Americans and White patients from Brazil (Table 1). The lack of an association between race and IL28B genotype in our South American patient population might partly explain the lack of association between race/ethnicity and viral kinetic parameters or viral response patterns in our recent reports 16, 17 . Indeed, preliminary results indicate that ~80% (of 353) of HCV-mono-infected individuals in Brazil are TC or TT with a similar distribution of CC/TC/TT genotypes between African Americans and Whites (Araujo et al manuscript in preparation).…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…In contrast, we did not identify a significant (p=0.5) difference in IL28B genotype frequencies between African Americans and White patients from Brazil (Table 1). The lack of an association between race and IL28B genotype in our South American patient population might partly explain the lack of association between race/ethnicity and viral kinetic parameters or viral response patterns in our recent reports 16, 17 . Indeed, preliminary results indicate that ~80% (of 353) of HCV-mono-infected individuals in Brazil are TC or TT with a similar distribution of CC/TC/TT genotypes between African Americans and Whites (Araujo et al manuscript in preparation).…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, there was a significantly higher proportion of IL28B genotype-CC in patients infected with HCV-genotype 3 than in patients infected with HCV-genotype 1 (Table S1), in agreement with recent studies that include HIV/HCV-coinfected 25 , and HCV-monoinfected individuals 27 . We previously reported higher first and faster second phase viral declines in genotype-3 compared to genotype-1 HIV/HCV co-infected patients 16 . In the current study, we identified a higher prevalence of IL28B CC-genotype in HCV genotype-3 cases, but no association between IL28B genotype and the second phase viral decline or the loss rate of HCV-infected cells, δ.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations